ISLAM PADA MASA KESULTANAN BANTEN - Maftuh, Maftuh (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2015)
For many observers, Banten is well known as an area where the population has a strict religious understanding onislamic law. Colonial officials and experts in Islamic studies such as Snouck Hurgronje and GF Pijper, testified that compared to other Muslims across Java , Muslim in Banten and Cirebon were stricter in practicing Islam . The phenomenon of the social life of the religious community in Banten is necessarily formed within a very long time span. This paper traces the root of the formation of public religious understanding ojMuslim in Banten. Using a socio-historical approach, this paper then leads to the conclusion that the sultan of Banten issued policies that had a greater emphasis to the adherence to the Shari'a rather than Sufism. Religious orientation on the fiqh-oriented can explain the Islamic militancy Banten community, as witnessed by the colonial officials, and even still can be seen up to this present moment.Key words: Jslamization, Sultanate, Banten